INTEGRATED NUTRIENT MANAGEMENT IN WHEAT (TRITICUM AESTIVUM) AND IT'S RESIDUAL EFFECT ON RICE (ORYZA SATIVA) IN NORTH-WESTERN HIMALAYAS - MANKOTIA, B.S.; THAKUR, R.C. (Annals of Agricultural Research, 2014)
A field experiment was conducted during 2001-02 to 2003-04 at CSK HP Krishi Vishvavidyalaya, Palampur, to study the effect of organic sources and fertility levels on wheat and their residual effect on rice. Five organic sources, viz. S1 : FYM 5.0 t /ha on dry weight basis, S2: paddy straw, S3 : soybean straw, S4: FYM 2.5 t/ha + paddy straw and S5 : FYM 2.5 t/ha + soybean straw (paddy and soybean straw were applied to supply N as in Si) were applied in all possible combinations with 3 fertility levels viz. 50, 100 (120 kg N + 26.2 kg P + 24.5 kg K/ha) and 150% of recommended fertilizer dose (RDF) to wheat crop. Sixteen treatments including one absolute control (no fertilizer and manure) were laid out in randomized block design with 3 replications. Organic sources and fertility levels significantly affected the plant height, yield attributes and productivity of wheat crop. Averaged over the fertility levels, S1 produced significantly higher wheat grain yield (41.7 q/ha) followed by S4 (31.6 q/ha), S5 (31.4 q/ha), S2 (28.5q/ha) and S3 (28.4 q/ha). Growth (plant height) and yield attributes viz, effective tillers per m row length, number of grains per spike and 1000 - grain weight supported the productivity levels. Based on the mean value of three years, gross return (Rs 37,294/ha), net return (Rs 18,184/ha) and benefit: cost ratio from wheat was higher in S1. Application of 100 and 150% of recommended dose of chemical fertilizers compared to 50% level increased wheat productivity by 5.3 (19.6%) and 10.7 (39.5%) q/ha, respectively. On an average, wheat productivity increased by 126.9 per cent with integrated nutrient management compared to absolute control (no manure/fertilizes).Residual effect of fertility levels applied to wheat improved the growth, yield parameters (number of tillers per unit area and 1000 grain weight) and paddy yield significantly up to 100% level where as residual effect of organic sources was not significant. Thus, high productivity (41.7 q/ha) and profitability of the wheat (in wheat - rice system) can be realized by applying FYM 5 t/ha alongwith l50% of recommended dose of chemical fertilizers. However, FYM 2.5 t/ha + paddy/soybean straws may also be used to obtain comparatively lower productivity levels (31.4-31.6 q/ha).